2012
DOI: 10.31258/jnat.14.1.7-13
|View full text |Cite
|
Sign up to set email alerts
|

Isoterma dan Termodinamika Adsorpsi Kation Cu2+ Fasa Berair pada Lempung Cengar Terpilar

Abstract: Pillared Cengar clay have been synthesized by two methods, first clay suspension is directly mixed into aqueous solution of hydroxy-aluminum polycations (WK) and second by mixing the clay suspension into the solution of sodium acetate and hydroxy-aluminumpolycations (SAK) sequentially. Both clays were calcined in air on atmospheric condition. Diffraction pola, surface morphology and cationexchange capacity of the pillared clays were characterized using X Ray Diffraction (XRD), Scanning Electron Microscopy (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…The qe for Mg/Cr-(COO)2 2-LDH was found greater than pristine making the intercalation had a larger surface area. Based on the literature study we conducted, this research showed a good ability for adsorption malachite green better than Mn/Fe LDH coating by polyethersulfone with the adsorption capacity of 13.49 mg/g [29]; CuCr-Polyoxometelate was conducted to remove malachite green with adsorption capacity 55 mg/g [11]; Sulfur-doped biochar had adsorption capacity of 30.18 mg/g [30]. Of all this study, the Mg/Cr-(COO)2 2was found to have a good ability for adsorption malachite green in aqueous solution.…”
Section: Resultsmentioning
confidence: 92%
“…The qe for Mg/Cr-(COO)2 2-LDH was found greater than pristine making the intercalation had a larger surface area. Based on the literature study we conducted, this research showed a good ability for adsorption malachite green better than Mn/Fe LDH coating by polyethersulfone with the adsorption capacity of 13.49 mg/g [29]; CuCr-Polyoxometelate was conducted to remove malachite green with adsorption capacity 55 mg/g [11]; Sulfur-doped biochar had adsorption capacity of 30.18 mg/g [30]. Of all this study, the Mg/Cr-(COO)2 2was found to have a good ability for adsorption malachite green in aqueous solution.…”
Section: Resultsmentioning
confidence: 92%
“…Derajat keasaman (pH) (Marcelia, 2014) Adsorbent yang telah banyak digunakan sebagai penjerap adalah karbon aktif, silica gel, dan mineral lempung seperti zeolit, bentonit, kaolit. Penggunaan media lempung dipilih agar proses adsorpsi dapat berjalan ekonomis, karena adsorben mineral mudah didapatkan, dan sebagai bagian dari produk lokal yang melimpah (Bahri et al, 2011) Penelitian ini dipilih bentonit sebagai adsorben dalam penjerapan logam Fe dalam limbah pelumas bekas. Adsorbent bentonit perlu diaktivasi terlebih dahulu untuk meningkatkan kemampuan penjerapannya.…”
Section: Temperaturunclassified
“…Modifikasi aktivasi permukaan adsorbent dapat dilakukan baik secara fisika maupun secara kimia. Aktivasi kimia dipilih untuk menghilangkan pengotor yang masih terdapat dalam bentonit (Bahri et al, 2011). Diharapkan kajian pengolahan limbah pelumas bekas menggunakan metode adsorpsi dengan bentonit sebagai adsorben, dan HCl sebagai aktivator dapat menghasilkan kajian keilmuan yang dapat mengurangi dampak pencemaran dari limbah pelumas bekas sebagai bahan berbahaya dan beracun (limbah B3) dengan menggunakan variasi konsentrasi HCl dan suhu adsorpsi sebagai variable penelitian bentonit sebagai adsorben.…”
Section: Temperaturunclassified
“…Lempung telah banyak dimanfaatkan dalam berbagai industri seiring dengan perkempangan ilmu pengetahuan mengenai manfaat lempung itu sendiri. Saat ini lempung sudah banyak dimanfaatkan sebagai adsorben (Bahri et al 2010), sebagai penyangga katalis (Lubis, 2009), sebagai penukar ion serta masih banyak pemanfaatan lain dari mineral lempung yang tergantung dari sifat meneralnya (Khairi et al 2004). Pemanfaatan lempung sebagai katalis, adsorben dan resin penukar kation, harus dimodifikasi karena lempung memiliki beberapa kelemahan diantaranya nilai kapasitas tukar kation yang rendah, mangandung banyak pengotor dan masih memiliki molekul air yang terdapat pada rongga lempung yang menyebabkan pori-porinya kecil (Laili et al 2014).…”
Section: Introductionunclassified